Simultaneous determination and determination of sildenafil and its active metabolite in human plasma using LC–MS/MS method. (7th July 2020) - Li, Lin‐ling; Zhang, Xiu‐jin; Zheng, Chao; Fan, Ming‐xia; Xu, Hao‐yun; Yi, Jin‐ling; Feng, Yan; Luo, Xi; Li, Wei‐hua; Cheng, Ze‐neng
Abstract: A sensitive and selective high‐performance liquid chromatography–tandam mass spectrometry (LC–MS/MS) method was developed and validated for the simultaneous quantification of sildenafil and its metabolite N ‐desmethyl sildenafil in human plasma. Sildenafil‐d8 was used as an internal standard. The analytes were extracted by precipitation extraction and chromatographed on a C18 column using mobile phase A of water (containing 0.1% formic acid) and mobile phase B of acetonitrile (containing 0.1% formic acid) with gradient elution. Quantification was done using multiple reaction monitoring mode to monitor the precursor‐to‐product ion transitions of m / z 475.4 → m / z 283.3 for sildenafil, m / z 461.4 → m / z 283.2 for N ‐desmethyl sildenafil and m / z 483.3 → m / z 108.1 for IS in positive ionization mode. The calibration curve was established over the range of 2.00–1, 000 ng/ml and the correlation coefficient was >0.99. The intra‐day and inter‐day relative standard deviations were <6.5% for sildenafil and 6.3% for N ‐desmethyl sildenafil respectively. Accuracy determinaed at four concentrations was 86.50–105.67% for sildenafil and 96.83–114.40% for N ‐desmethyl sildenafil. This method was successfully applied to a pharmacokinetic description of sildenafil and the effect of food intake on the pharmacokinetics of sildenafil was also demonstrated in healthy Chinese volunteers.